Strengthening adolescents’ critical health literacy and scientific literacy to tackle mis- and dis-information. A feasibility study in Switzerland - Fiordelli, Maddalena; Diviani, Nicola; Farina, Ramona; Pellicini, Paolo; Ghirimoldi, Alberto; Rubinelli, Sara (Frontiers in Public Health, 2023)
Objectives: We aimed to develop and pilot test the feasibility of a critical health literacy (CHL) and science literacy (SL) training course targeting secondary school students in Switzerland. Methods: Using a community-based participatory approach, we developed a two-block training program, the first centered on argumentation skills and the second on scientific skills. We combined an ex-cathedra and a flipped-classroom approach, providing students with a deep understanding of CHL and SL concepts and the translational capability of implementing theoretical notions to real case scenarios. The pilot study was designed as a one-group pretest-posttest quasi-experiment. Beyond socio-demographics, questionnaires included measures of CHL, SL, trust in science, and perceived quality of the course. Results: The curriculum was feasible and well-accepted by the target groups, teachers, and students. Students convincingly specified their perceived personal benefits associated with a positive change in CHL and SL scores after the training course. Conclusions: Training CHL and SL in secondary school students is feasible and can improve their competencies. Results from present study can inform a large-scale study.